2012
DOI: 10.19030/jber.v10i5.6983
|View full text |Cite
|
Sign up to set email alerts
|

Accounting, Culture, And Emerging Economies: IFRS In The BRIC Countries

Abstract: The culturally derived accounting orientations of four major emerging economies, Brazil, Russia, India and China, the BRIC countries, are examined based on the Geert Hofstede work on cultural dimensions (Hofstede, 1980) and the hypothetical derivation of related accounting values by S. J. Gray. (Gray, 1988) Keywords: IFRS in BRIC Countries; Accounting Standards in BRIC Countries INTRODUCTIONhe area of comparative international accounting has developed as a significant focus of accounting research and educatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 23 publications
1
19
0
1
Order By: Relevance
“…Por outro lado, contrariando essas críticas, Borker (2012aBorker ( , 2012bBorker ( , 2013, convalidou a hipótese dos accounting values de Gray na era do IFRS em vários países (inclusive o Brasil), tendo verificado que o trabalho de Gray (1988) foi citado em mais de 650 pesquisas.…”
Section: Americano (Us Gaap) E O Internacional (Ifrs)unclassified
“…Por outro lado, contrariando essas críticas, Borker (2012aBorker ( , 2012bBorker ( , 2013, convalidou a hipótese dos accounting values de Gray na era do IFRS em vários países (inclusive o Brasil), tendo verificado que o trabalho de Gray (1988) foi citado em mais de 650 pesquisas.…”
Section: Americano (Us Gaap) E O Internacional (Ifrs)unclassified
“…The BRIC countries are often paired into two groups: Brazil/Russia and India/China. The former group is identified as large land mass countries with relatively low populations that are rich in natural resources and the latter as having two of the world's largest populations (Borker, 2012).…”
Section: Financial Reporting In the Bric Countriesmentioning
confidence: 99%
“…While the adoption/convergence with IFRS is a high priority for the BRIC countries due to their need for continued access to foreign capital (Borker, 2012), there exists some reluctance from individual countries' regulators À taxation issues being one of the reasons. In addition, differences in the legal systems, financing systems and culture of the BRIC countries may not be resolved by the adoption of IFRS.…”
Section: Financial Reporting In the Bric Countriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies had shown there an influence of cultural towards accounting standards adaptability (Borker, 2012;Hashim, 2012;Young, 2013), use of technology (Connolly, 2011;Fang, Benamati, and Lederer, 2011;Leidner and Kayworth, 2006) and XBRL voluntary filing (Leidner and Kayworth, 2006;Chunhui Liu and Farrell, 2013). Gray (1988) had extend the Hofstede cultural theory in the context of accounting level for better understanding of the different values in accounting standard adoption.…”
Section: Introductionmentioning
confidence: 99%